2017
DOI: 10.1542/peds.2017-0203
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Differences in Antibiotic Use for Viral Illness in Emergency Departments

Abstract: Compared with NH white children, NH black and Hispanic children were less likely to receive antibiotics for viral ARTIs in the PED. Future research should seek to understand why racial and ethnic differences in overprescribing exist, including parental expectations, provider perceptions of parental expectations, and implicit provider bias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
94
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 31 publications
(27 reference statements)
9
94
2
Order By: Relevance
“…T A G G E D P PREVIOUS RESEARCH INDICATES that there are racial and ethnic differences in rates of diagnostic testing and clinical interventions of pediatric patients treated in the pediatric emergency department (PED). 1,2 In 1 study, non-Hispanic white patients were more likely to receive analgesics for abdominal pain compared to non-Hispanic black or Hispanic patients. 2 In another study, non-Hispanic white patients were more likely to receive antibiotics for viral illnesses compared to non-Hispanic black or Hispanic patients, regardless of provider type, insurance status, or acuity.…”
Section: T a G G E D P What's Newmentioning
confidence: 99%
See 1 more Smart Citation
“…T A G G E D P PREVIOUS RESEARCH INDICATES that there are racial and ethnic differences in rates of diagnostic testing and clinical interventions of pediatric patients treated in the pediatric emergency department (PED). 1,2 In 1 study, non-Hispanic white patients were more likely to receive analgesics for abdominal pain compared to non-Hispanic black or Hispanic patients. 2 In another study, non-Hispanic white patients were more likely to receive antibiotics for viral illnesses compared to non-Hispanic black or Hispanic patients, regardless of provider type, insurance status, or acuity.…”
Section: T a G G E D P What's Newmentioning
confidence: 99%
“…2 In another study, non-Hispanic white patients were more likely to receive antibiotics for viral illnesses compared to non-Hispanic black or Hispanic patients, regardless of provider type, insurance status, or acuity. 1 Although racial and ethnic disparities among pediatric patients are widely known, disparities in PED management among patients and families with language barriers and limited English proficiency have not been as thoroughly investigated.…”
Section: T a G G E D P What's Newmentioning
confidence: 99%
“…Two retrospective cohort studies also reported white patients to receive more antibiotics compared to black and Hispanic; however, these analyses only included children. 22,23 To date, our study is the only available report that identified racial differences in antibiotic prescribing for sinusitis in adults. Further investigation in this area is warranted.…”
Section: Discussionmentioning
confidence: 95%
“…These considerations suggest that vaccines against pathogens that cause respiratory infections, such as Bordetella pertussis, Streptococcus pneumoniae, influenza virus, and respiratory syncytial virus, may substantially reduce the exposure of a broad range of pathogenic bacterial species to antibiotics, via prevention of bystander selection. Notably, this includes vaccines that prevent viral respiratory infections, which are often inappropriately treated with antibiotics (14) and perhaps prevent bacterial secondary infections that might be appropriately treated if they occurred (15) . We have described an approach for using estimates of bystander exposures to estimate how vaccines could reduce exposure across various non-target pathogens.…”
Section: Discussionmentioning
confidence: 99%